2014
DOI: 10.1007/s13312-014-0383-2
|View full text |Cite
|
Sign up to set email alerts
|

Growth of children with juvenile idiopathic arthritis

Abstract: Children with juvenile idiopathic arthritis do not have significantly lower values of anthropometric parameters compared to controls. Significant restriction in height and weight is seen in systemic onset disease, and growth velocity is significantly reduced in rheumatoid factor positive subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 13 publications
4
10
1
Order By: Relevance
“…Most of the children (88.7%) presented before 10 years of age. This data is similar to most of the studies in the literature, which shows a mean age of onset below 10 years of age . Kunjir et al .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Most of the children (88.7%) presented before 10 years of age. This data is similar to most of the studies in the literature, which shows a mean age of onset below 10 years of age . Kunjir et al .…”
Section: Discussionsupporting
confidence: 91%
“…JIA shows female predilection in our study. This is in concordance with most of the data from Western countries and South Africa; however, it is in contrast to other studies from India, which show a male preponderance. The similarity of our data to Western countries probably is due to the better gender ratio as well as better care enjoyed by girls in our state compared to most other states in the country.…”
Section: Discussionsupporting
confidence: 91%
“…Average age at diagnosis of the population was 7.44 ± 4.52 years, which was in line with other studies [29] [36] Both the occurrence and severity of height retardation were predicted by the low age at diagnosis of the patient; while the no effect was observed on weight growth. This is generally …”
Section: Effect Of Age At Diagnosissupporting
confidence: 90%
“…A prospective case-control study from India found no significant difference between JIA children and healthy controls. Authors compared weight, height, body mass index and growth velocity over 6 months of children with JIA versus healthy children [29]. This shows relatively high proportion of growth impairment among our study population, which points towards the existence of other probable risk factors.…”
Section: Epidemiology Of Growth Retardation In Jiamentioning
confidence: 71%
See 1 more Smart Citation